Implementation and 1-year follow-up of the cardiovascular ICU standardised handover - Monica Lupei; Nishkruti Munshi; Alexander M Kaizer; Luke Patten; Joyce Wahr (BMJ Open Quality)
Background Miscommunication during clinical handover can lead to partial information transfer and healthcare provider dissatisfaction. We hypothesised that a quality improvement project to standardise the cardiovascular intensive care unit (CVICU) handover could improve healthcare provider satisfaction and reduce information omission.Methods After institutional review board approval, the operating room (OR) to CVICU handover was audited prior, post and 1 year after standardisation implementation. The medical information transferred, healthcare provider participation and satisfaction, and patient outcome data were collected. Additionally, surveys were sent to the OR and CVICU staff by email.Results There were 68 handover processes observed. The odds of greater satisfaction with handover for providers were 18 times higher with the process post implementation (p<0.0001) and 26 times higher 1 year after implementation (p<0.0001). There was statistically significant difference between intensive care unit resident presence (45% vs 76% vs 91%, p=0.004), surgical faculty presence (10% vs 36% vs 45%, p=0.034) and surgical fellow presence (15% vs 64% vs 62%, p=0.001) between the three time periods. More information related to the surgeon (5% vs 52% vs 27%, p=0.002), the medical history (65% vs 96% vs 91%, p=0.014) and the cardiopulmonary bypass (47% vs 88% vs 76%, p=0.017) was conveyed. The duration of mechanical ventilation was shorter after implementation (2.2±2.6 days vs 1.2±1.9 days vs 0.5±1.2 days, p=0.026).Conclusions One year after the OR to CVICU standardised handover implementation, the healthcare provider satisfaction remained increased, more team members participated and the information transfer increased. Although some clinical outcomes improved, further studies are recommended to prove causality.